Analisis Forensik Digital Pada Whatsapp Dan Facebook Menggunakan Metode NIST - Ruslan, Takdir; Riadi, Imam; Sunardi, Sunardi (JURNAL FASILKOM, 2023)
Technological developments can make it easier for Smartphone users to share various kinds of information using instant messaging applications such as Facebook Messenger and WhatsApp, the features contained in these instant messaging applications can send messages in the form of text, audio, images, videos and documents. The increase in the number of users of instant messaging applications also has a negative impact, namely the emergence of individuals who abuse instant messaging applications for digital crimes such as fraud, pornography, and drug sales. Disclosure of crimes requires valid digital evidence. In conducting investigations of digital crime cases, digital evidence is needed to solve them. Retrieval of digital evidence requires a forensic process of the physical evidence that has been obtained. This research focuses on the forensic process to obtain digital evidence from an Android Smartphone in the form of audio and video in the Facebook Messenger and WhatsApp applications. The forensic tools used in this research are Oxygen Forensic Pc Suite 2014, MOBILedit Forensic, Belkasoft evidence, and Magnet Axiom. The research uses a framework from the National Institute of Standards and Technology (NIST). The results of the research using the NIST method on an Android Smartphone were that Belkasoft succeeded in recovering deleted data with a percentage of 50% audio and 41% video on the WhatsApp application while on Facebook Messenger only 8.33% audio and 41% video, Magnet Axiom with a data percentage of 100%. audio and 100% video while Facebook Messenger has 8.33% audio and 5% video, on MOBILedit with a percentage of 0% on both applications, and Oxygen manages to return 16.67% audio and 23.5% video from the WhatsApp application and 0% for Facebook Messenger